2011
DOI: 10.1097/adm.0b013e3181e6ad48
|View full text |Cite
|
Sign up to set email alerts
|

Earning “Take-Home” Privileges and Long-Term Outcome in a Methadone Maintenance Treatment Program

Abstract: The group with the shortest time (3 to 6 months) to the achievement of first take-home dose had the best outcome. Further studies are needed to characterize this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…We had reported that patients who managed to achieve even one THD had longer retention in MMT, and those who achieved their fi rst THD the quickest, had the best outcome (Peles et al 2011a). They also showed as would be expect, that the patients with a higher number of THD were with better characteristics than those with a lower THD number or no-THD at all.…”
Section: Study Samplementioning
confidence: 68%
See 2 more Smart Citations
“…We had reported that patients who managed to achieve even one THD had longer retention in MMT, and those who achieved their fi rst THD the quickest, had the best outcome (Peles et al 2011a). They also showed as would be expect, that the patients with a higher number of THD were with better characteristics than those with a lower THD number or no-THD at all.…”
Section: Study Samplementioning
confidence: 68%
“…The policy of the Adelson MMT Clinic to dispense " take-home " has already been described (Peles et al 2011a). The minimal threshold requirement is for a minimum of 3 months with no drugs in urine in order to achieve the fi rst THD, 8 months to achieve 1 week (6-THD) and more than 2 years to achieve the maximal THD of 2 weeks (13-THD).…”
Section: Study Samplementioning
confidence: 98%
See 1 more Smart Citation
“…The unregistered status of methadone in Kazakhstan does not allow for take-home doses, and as a result MAT is often interrupted when patients must undergo inpatient treatment in other medical facilities or move away from their home cities. Such restrictive dispensing policy is maintained despite a growing body of evidence that take-home doses of methadone improve treatment outcomes and reduce health care costs [3, 33, 34]. In addition MAT is not available in the penitentiary system, which not only results in treatment interruption for incarcerated patients but also seriously limits the health care system's ability to control HIV and other blood-borne diseases among opioid dependent prison population.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we did not exclude them from the study. Importantly, all the participants in the methadone maintenance group fulfilled the American Society of Addiction Medicine (ASAM) criteria for take-home dose privilege, which include 3 month of abstinence together with an indication that the patient is stable, and responsible to keep the dose safe at home and drink it at due time (Peles et al, 2011). Exclusion criteria included age above 55 and positive urine for any drugs in the last 3 months.…”
Section: Participantsmentioning
confidence: 99%